PROFIL PENCAPAIAN TUGAS PERKEMBANGAN USIA LANJUT DI PARAK JIGARANG KELURAHAN ANDURING KECAMATAN KURANJI KOTA PADANG - Saputra, Randi; Ibrahim, Indra; Nofrita, Nofrita (Bimbingan dan Konseling, 2013)
Development of the elderly is the last development stage ofÂ human life process. Elderly development is closing period ofÂ life. This research was examined to describe profile of elderly achievement in Parak Jigarang, Padang. This research was designed in descriptive design. Population ofÂ this research is all of elderly in Kuranji especially Parak Jigarang. Total of population and sample of this research is 31 people. Technique of sample is total sampling where the population is smaller than 100 people. The result of this research; 1) The elderly did not achieve the adaptation of their physic condition. 2) The elderly did not achieve the resign period. 3) The elderly did not achieve the adaptation of the death of their couple optimally. 4) The elderly did not achieve the social rule. The researcher recommended to: (1) The elderly have to be able to consider and to achieve their achievement in their age. (2) Family has to be care to the elderly, also help them for achieving their achievement in their last life stage effectively. (3) Societies have to build interaction with the elderly. So, there will no negative influence. (4) The student of Counseling Department who will do PPLBKT, try to be selective in giving counseling especially for the elderly. (5) Counseling Department is hoped to implement PPLBKT and distribute the student to Parak Jigarang for doing counseling continuously.